Multiscale Modeling of the Thermal Conductivity of Wood and Its Application to Cross-Laminated Timber - Saavedra-Flores, E; Diaz-Matus, A; Yanez-Cart, S; Guzman-Inostroza, C; Vasco-Calle, D; Pina, J (Elsevier Masson SAS, 2019)
In this work, a computational homogenization-based multiscale modeling strategy is adopted to compute the thermal conductivity of wood and to study the thermal performance of cross-laminated timber. In order to determine the thermal conductivity of wood within a multiscale modeling framework, the behavior of its microscopic constituents is investigated. By following a bottom-up approach, the computational homogenization of the material is sequentially carried out at the nanometer level and then, at the micrometer scale, resulting in the effective thermal conductivity of wood. Furthermore, the influence of the cellulose volume fraction and the microfibril angle on the cell-wall material s thermal conductivity is analyzed. These studies lead to the effective thermal conductivity components of 0.308 W/(m K), 0.107 W/(m K), and 0.115 W/(m K), along the longitudinal, radial and tangential axes of wood, respectively. These values are compared to published data and are validated successfully. Several macroscopic applications are investigated. In particular, the influence of two types of panel-to-panel connections on the thermal dissipation is assessed in a cross-laminated timber panel. © 2019 Elsevier Masson SAS